Unusual Presentation of Light Chain Deposition Disease: A Case Report - Arora, Disha (J Clin Diagn Res, 2016)
Light Chain Deposition Disease (LCDD) is a rare disease characterized by deposition of monoclonal non-amyloid light chains in multiple organs. We report an unusual histologic manifestation of LCDD in a 55-year-old female patient, who presented with nephrotic syndrome and an increased serum creatinine. This case of LCDD had features of cast nephropathy on biopsy which is diagnostic of myeloma kidney, when the patient was clinically asymptomatic. Serum electrophoresis showed no abnormal band. There was no other evidence of a B-cell clonal disorder or amyloidosis. Following chemotherapy, improvement in renal function correlated with a reduction in circulating light-chain levels.